The effectiveness of nitrofurantoin, fosfomycin and trimethoprim for the treatment of cystitis in relation to renal function. (October 2020) - ten Doesschate, T.; van Haren, E.; Wijma, R.A.; Koch, B.C.P.; Bonten, M.J.M.; van Werkhoven, C.H.
Abstract: Objectives: We evaluated the effect of renal function on clinical failure rates of nitrofurantoin, fosfomycin and trimethoprim for the treatment of cystitis in primary care. Methods: Data were retrospectively obtained from 78 Dutch general practitioner (GP) practices between 2013 and 2019. Eligible episodes in patients (>11 years) were those requiring 5 days of nitrofurantoin (NF5), single-dose fosfomycin–trometamol (FT1), 3 days of trimethoprim (TMP3) for uncomplicated cystitis, or 7 days of nitrofurantoin (NF7) or trimethoprim (TMP7) for complicated cystitis. Clinical failure was defined as second antibiotic prescription for cystitis or pyelonephritis within 28 days post-prescription. Mixed effects regression analysis was used, with patient and GP practice as random effects and demography, comorbidity, and cystitis history as fixed effects. Results: Adjusted odds ratios (aORs) for clinical failure per 10mL/min decrease in estimated glomerular filtration rate (eGFR) were 1.05 (95% CI: 1.01–1.09) for NF5 (n = 24, 591), 0.96 (95% CI: 0.92–1.01) for FT1 (n = 5359), 0.98 (95% CI: 0.89–1.08) for TMP3 (n = 1064), 1.05 (95% CI: 1.02–1.09) for NF7 (n = 10, 628) and 1.02 (95% CI: 0.93–1.14) for TMP7 (n = 831). In uncomplicated cystitis and eGFR ≥60 mL/min, clinical failures occurred in 14.6% (1895/12 980) of NF5-treated, 20.7% (266/1283) of FT1-treated (aOR versus NF5 1.37, 95% CI 1.18–1.59) and 20.8% (66/318) of TMP3-treated patients (aOR 1.42, 95% CI 1.07–1.87 versus NF5). In uncomplicated cystitis and eGFR <60 mL/min, FT1 resulted in 16.0% (39/244) and NF5 in 23.3% clinical failures (110/472), aOR: 0.61, 95% CI: 0.39–0.95). Conclusions: In eGFR ≥60 mL/min treatment with fosfomycin or trimethoprim for uncomplicated cystitis was associated with more clinical failure than treatment with nitrofurantoin, while in eGFR <60 mL/min nitrofurantoin was associated with more clinical failure than fosfomycin–trometamol. Renal function, if known, should be considered in the clinical decision-making for cystitis treatment.